Role of Transforming Growth Factor‐beta1 in Cyclosporine‐Induced Epithelial‐to‐Mesenchymal Transition in Gingival Epithelium. Issue 1 (1st January 2015) - Fu, Martin M.; Chin, Yu‐Tang; Fu, Earl; Chiu, Hsien‐Chung; Wang, Li‐Yu; Chiang, Cheng‐Yang; Tu, Hsiao‐Pei
Abstract : Background: It has been proposed that cyclosporin A (CsA) may induce epithelial‐to‐mesenchymal transition (EMT) in gingiva. The aims of the present study are to confirm the notion that EMT occurs in human gingival epithelial (hGE) cells after CsA treatment and to investigate the role of transforming growth factor beta1 (TGF‐β1) on this CsA‐induced EMT. Methods: The effects of CsA, with and without TGF‐β1 inhibitor, on the morphologic changes of primary culture of hGE cells were examined in vitro. The changes of protein and messenger RNA (mRNA) expressions of two EMT markers (E‐cadherin and alpha‐smooth muscle actin) in the hGE cells after CsA treatment with and without TGF‐β1 inhibitor were evaluated with immunocytochemistry and real‐time polymerase chain reaction. Results: The epithelial cells became spindle‐like, elongated, and disassociated from neighboring cells and lost their original cobblestone monolayer pattern when CsA was added. However, the epithelial cells stayed in their original cobblestone morphology with treatment of TGF‐β1 inhibitor on top of the CsA treatment. When CsA was given, the protein and mRNA expressions of E‐cadherin and α‐SMA were significantly altered, and these alterations were significantly reversed with pretreatment of TGF‐β1 inhibitor. Conclusions: CsA could induce Type 2 EMT in gingiva by changing the morphology of epithelial cells and altering the EMT markers/effectors. The CsA‐induced gingival EMT is dependent or at least partially dependent on TGF‐β1.